Predictive role of preoperative sarcopenia for long-term survival in rectal cancer patients: A meta-analysis. - Qiutong Su; Jia Shen (PLoS ONE)
Purpose To identify the predictive role of sarcopenia in long-term survival among rectal cancer patients who underwent surgery based on available evidence. Methods The Medline, EMBASE and Web of Science databases were searched up to October 20, 2023, for relevant studies. Overall survival (OS), disease-free survival (DFS) and cancer-specific survival (CSS) were the endpoints. Hazard ratios (HRs) and 95% confidence intervals (CIs) were combined to evaluate the association between sarcopenia and survival. Results Fifteen studies with 4283 patients were included. The pooled results demonstrated that preoperative sarcopenia significantly predicted poorer OS (HR = 2.07, 95% CI = 1.67-2.57, P<0.001), DFS (HR = 1.85, 95% CI = 1.39-2.48, P<0.001) and CSS (HR = 1.83, 95% CI = 1.31-2.56, P<0.001). Furthermore, subgroup analysis based on neoadjuvant therapy indicated that sarcopenia was a risk factor for worse OS and DFS in patients who received (OS: HR = 2.44, P<0.001; DFS: HR = 2.16, P<0.001) but not in those who did not receive (OS: HR = 2.44, P<0.001; DDFS: HR = 1.86, P = 0.002) neoadjuvant chemoradiotherapy. In addition, subgroup analysis based on sample size and ethnicity showed similar results. Conclusion Preoperative sarcopenia is significantly related to poor survival in surgical rectal cancer patients and could serve as a novel and valuable predictor of long-term prognosis in these patients.